Taxi wars: Uber in China - REDDY, Srinivas K. (Institutional Knowledge at Singapore Management University, 2017)
The case describes how Uber, the mobile ride hailing service provider, made an entry into China in July 2014 and, after facing stiff competition from local players, was forced to sell its stake and exit the country two years later. Prior to Uber’s entry, China’s major players, Didi and Kuaidi, had been competing fiercely to attract both riders and drivers by offering steep discounts and subsidies. To compete with the two local players, Uber established a strategic partnership with Baidu, one of China’s largest Internet companies. Shortly after, Didi and Kuaidi merged to form a formidable, monopolistic competitor against Uber, controlling almost 95% of the ride hailing business. Uber’s future in China appeared bleak. It had been losing over US$1 billion a year in China since its entry into the market. Faced with such stiff competition and recurring loses, Uber sold its stake and exited China in August 2016. Now Travis Kalanick, CEO of Uber, would have to assess what went wrong, what could have been done differently, and what should be the next steps for expanding and increasing Uber’s market share in Asia.